β-Ta2O5 thin film for implant surface modification triggers superior anti-corrosion performance and cytocompatibility of titanium - Beline, Thamara; de Almeida, Amanda B.; Azevedo Neto, Nilton F. [UNESP]; Matos, Adaias O.; Ricomini-Filho, Antônio P.; Sukotjo, Cortino; Smeets, Paul J.M.; da Silva, José H.D. [UNESP]; Nociti, Francisco H.; Barão, Valentim A.R. (Elsevier, 2020)
In this study, β-tantalum oxide (β-Ta2O5) thin film was synthesized via magnetron sputtering to improve the surface properties, cytocompatibility and electrochemical stability of titanium. X-ray diffraction analysis confirmed a crystalline orthorhombic phase of Ta2O5 film on the β-Ta2O5 experimental surface. A granular structure with a complex and hierarchical nature was demonstrated by atomic force microscopy. Ta2O5-treated surfaces exhibited greater roughness and hydrophilicity compared with untreated titanium discs (control). Enhanced electrochemical stability in simulated body fluid (pH 7.4) was noted for Ta2O5-treated surfaces wherein higher values of charge transfer resistance, nobler corrosion potential, and lower capacitance, corrosion current density, and corrosion rate values were observed vs untreated control. Real-time monitoring of albumin and fibrinogen proteins adsorption by an electrochemical quartz crystal microbalance disclosed similar protein interactions for control and Ta2O5-treated discs, with higher fibrinogen adsorption rates for Ta2O5-treated surfaces. Cell culture assays (MC3T3-E1 cells) demonstrated that Ta2O5-treated discs featured greater in vitro mineral nodule formation, normal cell morphology and spreading, and increased mRNA levels of runt-related transcription factor 2 (Runx-2), osteocalcin (Ocn), and collagen-1 (Col-1). Therefore, it can be concluded that β-Ta2O5 thin films may be considered a promising strategy to trigger superior long-term stability and biological properties of titanium implants.
Keywords: Biomaterials; Corrosion; Dental implants; Magnetron sputtering; Protein adsorption; Tantalum oxide